Investigation of risk management and crisis management which is based on three cases of real-life business - YUANQIAN, ZHANG (2010)
The purpose of this research is to investigation the importance of risk management and crisis management based on three real-life cases, and to tackle how organizations can enhance their ability to identify and react to warning signals or even crisis, as well as the crisis management process is be summarized. These real-life examples includes BP’s refinery crisis in Taxes City in 2005, Merck’s Vioxx withdraw in 2004, and Citibank Japan closed one year as money laundering in 2004. The following approaches will be followed: A wide range of literatures on risk management and crisis management have been reviewed. To examine the validity and the application of these theories, real-life examples have then been adopted. Different research questions are set up to do better analysis. On the other hands, the analyses of these three real cases are based on three different periods: the year before the crisis, the year of crisis, and the year after the crisis. Furthermore, this research analyses annual reports of these three firms. The findings from the cases analysis indicate the lessons from BP, Merck and Citibank Japan, and the crisis management process is summarized. The examination of real-life organizational crisis proves the validity of the above leading author theory on crisis management analysis. In terms of these three cases, research results show that the lessons learned from these organizations can be imported to other organizations.